(untitled) (Scientific journal of the Fergana State University, 2026)
This article analyzes the issues of developing non-verbal communicative competence in teaching Russian as a foreign language from both theoretical and practical perspectives. For beginner-level students, the importance of facial expressions, gestures, body language, intonation, and visual aids in the language learning process is emphasized. Furthermore, the article substantiates the significance of using innovative methods of non-verbal communication, interactive technologies, and considering intercultural differences in the process of teaching a foreign language.